Comparison of Prognostic Models in Acute Liver Failure: Decision is to be Dynamic - Saluja, Vandana (Indian J Crit Care Med, 2019)
BACKGROUND AND AIMS: Acute liver failure (ALF) is a rare disease entity with a high mortality. Management is dependent on accurate prognostication. MATERIALS AND METHODS: One hundred consecutive patients presenting with ALF were prospectively evaluated. The King's college criteria (KCC), ALF early dynamic model (ALFED), sequential organ failure assessment (SOFA) score, and acute physiology and health evaluation II (APACHE II) scores were compared to predict mortality. RESULTS: There were significant differences in means of all the scores between survivors and nonsurvivors. The SOFA 48 hours had the highest area under receiver operating characteristic curve (AUC) (0.857) closely followed by the ALFED score (0.844). The optimal cutoff for the SOFA score at 48 hours to predict subsequent survival outcome is ≥10 and for the ALFED score is ≥5. Sequential organ failure assessment 48 hours had a good sensitivity of 87%, and the ALFED score showed a good specificity of 84%. The decision curve analysis showed that between a threshold probability of 0.13 and 0.6, use of the SOFA score provided the maximum net benefit and at threshold probabilities of >0.6, the use of ALFED score provided the maximum clinical benefit. CONCLUSION: Dynamic scoring results in better prognostication in ALF. The SOFA 48 hours and ALFED score have good prognostication value in nonacetaminophen-induced liver failure. HOW TO CITE THIS ARTICLE: Saluja V, Sharma A, Pasupuleti SSR, Mitra LG, Kumar G, Agarwal PM. Comparison of Prognostic Models in Acute Liver Failure: Decision is to be Dynamic. Indian J Crit Care Med 2019;23(12):574–581.